2015
DOI: 10.4238/2015.december.16.13
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of MACC1 expression enhances cisplatin sensitivity in SKOV-3/DDP cells

Abstract: ABSTRACT. The aim of this study was to investigate the correlation between MACC1 expression and resistance to cisplatin (DDP) in DDPresistant human epithelial ovarian cancer SKOV-3 cells (SKOV-3/DDP). MACC1 mRNA and protein expression levels in SKOV-3 and SKOV-3/DDP cells were detected by reverse transcriptase polymerase chain reaction and western blot. The SKOV-3/DDP cells were divided into 5 groups: control, shVect (transfected with p-super-EGFP-1 plasmid), pshMACC1 (transfected with psuper-EGFP-shMACC1 plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In fact, this is not the first time MACC1 has been found to play a role in drug resistance. It was reported that MACC1 overexpression induced cisplatinum resistance in ovarian cancer (28,29). Therefore, it is possible and reasonable that MACC1 contributes to oxaliplatin resistance in GC.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, this is not the first time MACC1 has been found to play a role in drug resistance. It was reported that MACC1 overexpression induced cisplatinum resistance in ovarian cancer (28,29). Therefore, it is possible and reasonable that MACC1 contributes to oxaliplatin resistance in GC.…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian cancer is associated with malignant tumor mortality in women worldwide. According to the GLOBOCAN series reported by the International Cancer Institute, female cancer has a relatively poor prognosis with a 32.5% mortality rate [ 1 ]. Ovarian cancer is one of the most typical gynecological malignancies, with 21750 newly diagnosed cases each year, leading to high morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%